A Cross-National Study of Consumer Spending Behavior: The Impact of Social Media Intensity and Materialism. Issue 4 (8th August 2018) - Thoumrungroje, Amonrat
ABSTRACT: The ubiquity of Internet, mobile devices, and online social media platform has undeniably altered consumer lifestyles and business conduct globally. To explore the influences of social media on consumer behavior, this study applied the "self-regulation" concept and a cross-cultural conceptualization of "self" to propose a model explicating how social media intensity directly and indirectly—through materialism—impact consumers' credit overuse, conspicuous consumption, and impulse buying. Using data collected from the U.S. and South Korea, social media intensity strongly influences consumer spending in the American sample but has no effect on credit overuse behavior in the South Korean sample.